2016
DOI: 10.3847/2041-8205/819/2/l32
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Spectroscopy of a Balmer-Dominated Shock in the Cygnus Loop: An Extremely Thin Cosmic-Ray Precursor?

Abstract: We present high-resolution long-slit spectroscopy of a Balmer-dominated shock in the northeastern limb of the Cygnus Loop with the Subaru high dispersion spectrograph. By setting the slit angle along the shock normal, we investigate variations of the flux and profile of the Hα line from preshock to postshock regions with a spatial resolution of ∼4×10 15 cm. The Hα line profile can be represented by a narrow (28.9±0.7 km s −1 ) Gaussian in a diffuse region ahead of the shock, i.e., a photoionization precursor, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…2), seemingly composed of two long pairs of filaments in the first-epoch images can now be seen to consist of many delicate and overlapping filaments along with faint but noticeable diffuse emission in between filaments. This complex morphology is similar to that seen in the nonradiative filaments along the northern and eastern limbs of the Cygnus Loop SNR where the shock front is seen edge on and gently warped as it moves through an interstellar medium with small density variations on large scales (Hester et al 1986(Hester et al , 1994Levenson et al 1998;Blair et al 1999Blair et al , 2005Medina et al 2014;Katsuda et al 2016).…”
Section: Filament Morphologysupporting
confidence: 70%
“…2), seemingly composed of two long pairs of filaments in the first-epoch images can now be seen to consist of many delicate and overlapping filaments along with faint but noticeable diffuse emission in between filaments. This complex morphology is similar to that seen in the nonradiative filaments along the northern and eastern limbs of the Cygnus Loop SNR where the shock front is seen edge on and gently warped as it moves through an interstellar medium with small density variations on large scales (Hester et al 1986(Hester et al , 1994Levenson et al 1998;Blair et al 1999Blair et al , 2005Medina et al 2014;Katsuda et al 2016).…”
Section: Filament Morphologysupporting
confidence: 70%
“…Furthermore, linear analysis and several numerical simulations show that the CR precursor generates magnetic-field fluctuation (Bell, 1978(Bell, , 2004Niemiec et al, 2008;Ohira et al, 2009;Riquelme & Spitkovsky, 2009;Ohira & Takahara, 2010;Caprioli & Spitkovsky, 2013). Recently, Katsuda et al (2016) found that the upstream plasma of the SNR Cygnus loop is abruptly heated in the vicinity of shocks explained via damping of magnetic-field fluctuation in an unresolved thin CR precursor. However, the CR precursor of SNRs has never been directly imaged so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that the ISM and ejecta of SNRs are not always fully ionized. In fact, the observed line profile of H α emission from SNRs supports that some SNR shocks are propagating to the partially ionized ISM (Chevalier & Raymond 1978;Katsuda et al 2016). It was proposed that many plasma instabilities are excited by the ionization around a collisionless shock in the partially ionized plasma Ohira et al 2009;Ohira & Takahara 2010;Ohira 2014).…”
Section: Introductionmentioning
confidence: 60%